Corrigendum to “Dedifferentiated fat cells in polyglycolic acid-collagen nerve conduits promote rat facial nerve regeneration” [Regen Ther 11 (2019) 240–248] - Hiroshi Fujimaki; Hajime Matsumine; Hironobu Osaki; Yoshifumi Ueta; Wataru Kamei; Mari Shimizu; Kazuki Hashimoto; Kaori Fujii; Tomohiko Kazama; Taro Matsumoto; Yosuke Niimi; Mariko Miyata; et al. (Regenerative Therapy, 2020)
Introduction: Polyglycolic acid (PGA) nerve conduits, an artificial biodegradable nerve regeneration-inducing tube currently used in clinical practice, are effective in regenerating peripheral nerves. Dedifferentiated fat (DFAT) cells differentiate into various cells including adipocytes, osteoblasts, chondrocytes, skeletal muscle cells, and myofibroblasts, when cultured in appropriate differentiation-inducing conditioned culture medium. This study made a hybrid artificial nerve conduit by filling a PGA conduit with DFAT cells, applied the conduit to a rat facial nerve defect model, and investigated the facial nerve regenerative ability of the conduit. Methods: Under inhalational anesthesia, the buccal branch of the facial nerve in Lewis rats was exposed, and a 7-mm nerve defect was created. PGA nerve conduits were filled with DFAT cells, which were prepared from rat subcutaneous adipose tissue with type I collagen as a scaffold, and then grafted into the nerve defect sites in rats with a microscope (DFAT group) (n = 10). In other rats, PGA artificial nerve conduits alone were similarly grafted into the nerve defect sites (the control group) (n = 10). Reinnervation was confirmed at 13 weeks postoperatively by a retrograde tracer, followed by histological and physiological comparative studies. Results: The mean number of myelinated fibers was significantly higher in DFAT group (1606 ± 806) than in the control group (543 ± 478). Myelin thickness was also significantly lager in DFAT group (0.67 ± 0.02 μm) than in the control group (0.43 ± 0.01 μm). Although no significant difference was found in the amplitude of compound muscle action potential (CMAP) between DFAT group (2.84 ± 2.47 mV) and the control group (0.88 ± 0.56 mV), whisker motion was lager in DFAT group (9.22° ± 0.65°) than in the control group (1.9° ± 0.84°). Conclusions: DFAT cell-filled PGA conduits were found to promote nerve regeneration in an experimental rat facial nerve defect model.